Indirect effects of exercise on emotional eating through psychological predictors of weight loss in women. (1st December 2015) - Annesi, James J.; Mareno, Nicole
Abstract: An improved understanding of how weight-loss interventions might be tailored to improve emotional eating is required. This study aimed to assess mediation of the relationship between increased exercise and decreased emotional eating so that behavioral treatments might be optimized. After randomization, women with obesity (N = 108; mean age = 48 years) were assigned to either a previously tested treatment of manual-based self-help for nutrition and exercise plus brief phone follow-ups, or a new protocol of cognitive-behavioral methods of exercise support intended to carry-over psychological improvements to better controlled eating and weight loss. A community-based field setting was incorporated. Validated self-report measures were administered over 6 months. Significant overall improvements in exercise outputs, emotional eating, mood, and self-regulation and self-efficacy for controlled eating were found. The newly developed treatment protocol demonstrated significantly greater improvements in exercise outputs and self-regulation. In a multiple mediation analysis, changes in self-regulation, self-efficacy, and mood significantly mediated the relationship between changes in exercise and emotional eating. Changes in self-efficacy and mood were significant independent mediators. Within follow-up analyses, the substitution of emotional eating subscales that addressed specific moods, and a subscale of self-efficacy for controlled eating that addressed that factor specifically in the presence of negative emotions, yielded results generally consistent with those of the multiple mediation analysis. Results suggested a psychological pathway of exercise's association with emotional eating changes in women with obesity. Guided by the present findings, tailoring exercise support and leveraging it to induce specific psychological improvements might reduce emotional eating and improve weight-management outcomes. Highlights: Theory may be utilized to improve psychosocial predictors of emotional eating. Improvements in self-regulation, self-efficacy, and mood reduce emotional eating. Cognitive-behavioral methods and exercise benefit emotional eating and weight loss.